Renal safety of intravenous gadolinium‐enhanced magnetic resonance imaging in patients awaiting liver transplantation. Issue 11 (November 2015) - Shaffer, Katherine M.; Parikh, Mehul R.; Runge, Thomas M.; Perez, Sebastian D.; Sakaria, Sonali S.; Subramanian, Ram M.
<x xml:space="preserve">Abstract</x> Renal dysfunction in cirrhosis carries a high morbidity and mortality. Given the potential risk of contrast‐induced nephropathy associated with iodinated intravenous contrast used in computed tomography (CT), alternate contrast modalities for abdominal imaging in liver transplant candidates need to be examined. The purpose of this study was to examine the renal safety of magnetic resonance imaging (MRI) with gadolinium in patients awaiting liver transplantation. The study involved a retrospective analysis of 352 patients of abdominal MRI with low‐dose gadobenate dimeglumine (MultiHance) (0.05 mmol/kg) in patients with cirrhosis and without renal replacement therapy at a single center during the period from 2007 to 2013. For each case, serum creatinine before and within a few days after the MRI were compared. In addition, the patients were analyzed for the development of nephrogenic systemic fibrosis (NSF), a reported complication of gadolinium in chronic kidney disease. The pre‐MRI serum creatinine values ranged from 0.36 to 4.86 mg/dL, with 70 patients (20%) having values ≥ 1.5 mg/dL. A comparison of the pre‐ and post‐MRI serum creatinine values did not demonstrate a clinically significant difference (mean change = 0.017 mg/dL; P = 0.38), including those patients with a pre‐MRI serum creatinine ≥ 1.5 mg/dL. In addition, no cases of NSF were noted. In conclusion, our findings suggest that MRI with low‐dose gadobenate dimeglumine (MultiHance) is a nonnephrotoxic imaging modality in liver transplant candidates, and its use can be cautiously expanded to liver transplant candidates with concomitant renal insufficiency. Liver Transpl 21:1340‐1346, 2015. © 2015 AASLD.